A revision of the genus Podococcus (Arecaceae) - Valkenburg, J.L.C.H. van; Sunderland, Terry C.H. (2008)
A taxonomic revision of the palm genus Podococcus (Arecaceae) is presented. Two species are recognised:P. barteri, a species relatively widespread in a coastal band from Nigeria to the D. R. Congo and P. acaulis, a species previously considered conspecific to P. barteri, almost exclusively confined to Gabon. The taxonomic history, morphology, distribution and conservation status of the genus and each species are discussed